Determinan Efisiensi Teknis dan Sosial Ekonomi Produksi Kopi - Saputro, Arief Joko; Sari, Dina Kartika (Jurnal Sosial Ekonomi Pertanian, 2024)
Abstract Coffee farmers in Indonesia face several challenges, including low farmer productivity and skills. Smallholder farmers in Indonesia often experience low productivity and lack the skills and knowledge needed to improve their agricultural practices. This research aims to determine the level of technical efficiency of coffee production and determine the socio-economic factors that influence the technical inefficiency of coffee. This research was carried out in Prigen District, Pasuruan Regency, East Java. This location selection was done purposively. The data analysis method used is Data Envelopment Analysis to analyze the level of technical efficiency and Tobit regression analysis to analyze socio-economic factors that influence technical inefficiency. The research results mean total efficiency is 0.798 (TE CRS), pure technical efficiency (TE VRS) 0.873, and scale efficiency (SE) 0.911. Socio-economic factors that influence technical inefficiency include education, land area, and extension. The government and policymakers are expected to help farmers strengthen institutions and the role of agricultural extension workers to achieve efficient farming.